Монгол орон дахь газрын гадарга орчны инверси - М, Цоодол (Scientific transaction of the National University of Mongolia. Physics, 2022)
According to report of Mongolian 8 stations created general mode of surface of the earths temperatures inverses of air climate. Repeat established intensity and high of inverses is depends on territory of our country, feature environments current and changed by time.